Pentingnya Peningkatan Pendidikan Karakter dalam Menyongsong Pendidikan Abad 21 - Wahyuningtyas, Margareta Tri (Universitas Sebelas Maret, 2020)
This research is a literature study on the importance of character education in welcoming 21st century education which aims to prepare students for globalization. Education that integrates knowledge, skills, and attitudes, as well as mastery of ICT. These skills can be developed through various activity-based learning models that are in accordance with the characteristics of competencies and learning materials. The application of character education is carried out by three methods, namely: understanding, habituation, and example. The three main elements have not synergized in supporting the implementation of character education in schools.